Relationship explosive power and speed of the motor skill of the parties to the Supreme accurately crushing blow for badminton - Abbas, Saif (Journal of Physical Education, 2019)
Spoke in the first section in the introduction and the importance of the nature of the game of badminton and the physical requirements of a general strike and the skill requirements of the vast and, in particular, lies in the explosive power and speed mobility, the problem of research is to know the nature of the relationship between these attributes accurately skill, as well as goals and assumptions and areas, and came in the door the second concept of explosive power and speed as well as the concept of precision motor, Part III Vhtoy to the method of action research and field testing and research and statistical methods, while Part IV was the presentation, analysis and discussion of results, as stated in section V the conclusions confirmed the existence of a moral relationship between the accuracy of the skill and strength explosive speed and mobility, and the light of recommendations made in the service of process Ttoiber skill